EKSPERIMEN FILTER KREATIF DALAM FOTOGRAFI PRE-WEDDING DI MAXHELAR PHOTOGRAPHY - Wardana, Ketut Wisnu Jaya; Pramana, I Made Bayu; Octaviano, Amoga Lelo (Retina Jurnal Fotografi, 2022)
This study discusses Creative Filter Experiments in Pre-wedding Photography at Maxhelar Photography. This creative filter experiment in Pre-wedding Photography aims to show innovations about creative filters that can be used in Pre-wedding Photography. The purpose of this research is to find out how the results of creative filters are used in Pre-wedding Photography. This study also explains how to make creative filters and how to use creative filters in Pre-wedding Photography, this research also aims to be a reference and also hone creativity when doing prewedding photo shoots for writers and other photographers. The source studies used in this research are from journals, books and articles related to Pre-wedding photography, creative filters and understanding of work. The implementation method used when conducting the research is the method of observation, interviews, and work practices as well as several sources of data used, namely primary and secondary data. The results of this study indicate that creative filters in pre-wedding photography are new innovations that can be applied in pre-wedding photography, and as a support for beautifying the results of the photo shoot.